2004
DOI: 10.1103/physrevlett.92.047003
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous Electronic Structure Probed by Spin-Echo Experiments in the Electron Doped High-TcSuperconductorPr1.85et al.

Abstract: 63 Cu nuclear magnetic resonance (NMR) spin-echo decay rate (T −1 2 ) measurements are reported for the normal and superconducting states of a single crystal of Pr1.85Ce0.15CuO4−y (PCCO) in a magnetic field B0 = 9 T over the temperature range 2 K< T <200 K. The spin-echo decay rate is temperature-dependent for T < 55 K, and has a substantial dependence on the radio frequency (rf) pulse parameters below T ≈ 25 K. This dependence indicates that T −1 2 is strongly effected by a local magnetic field distribution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…They interpret these peculiar transport features as evidence for stripe formation in the underdoped n-type cuprates. In Pr 1.85 Ce 0.15 CuO 4 Zamborszky et al (2004) found signatures in the NMR spin-echo decay rate (1/T 2 ) for static inhomogeneous electronic structure. Similarly, Bakharev et al (2004) found via Cu NMR evidence for an inhomogeneous "blob-phase" (bubble) in reoxygenated superconducting Nd 1.85 Sr 0.15 CuO 4 .…”
Section: E Inhomogeneous Charge Distributionsmentioning
confidence: 90%
See 1 more Smart Citation
“…They interpret these peculiar transport features as evidence for stripe formation in the underdoped n-type cuprates. In Pr 1.85 Ce 0.15 CuO 4 Zamborszky et al (2004) found signatures in the NMR spin-echo decay rate (1/T 2 ) for static inhomogeneous electronic structure. Similarly, Bakharev et al (2004) found via Cu NMR evidence for an inhomogeneous "blob-phase" (bubble) in reoxygenated superconducting Nd 1.85 Sr 0.15 CuO 4 .…”
Section: E Inhomogeneous Charge Distributionsmentioning
confidence: 90%
“…This is in contrast to the hole-doped system where in the Néel state (x < 0.02) the internal field was constant (Borsa et al, 1995;Harshman et al, 1988), which has been taken as evidence for phase separation (Chou et al, 1993;Matsuda et al, 2002). Extensive NMR measurements have also been done by Bakharev et al (2004); Williams et al (2005); Zamborszky et al (2004) that have given important information about inhomogeneity in these systems. These measurements are discussed in more detail in Sec.…”
Section: Magnetic Field Dependencementioning
confidence: 98%
“…They found evidence for several distinct local environments, and argued that doped regions reached the percolation limit at x ≈ 0.14, at the phase boundary for superconductivity. Recent NMR studies have also found evidence of electronic inhomogeneity [255,256].…”
Section: Electron-doped Cupratesmentioning
confidence: 99%
“…17 On the other hand, it is expected that the increase of doping density may lead to the increase of disorders due to the potential fluctuations created by the dopants. Consistent with this statement, very recent spin-echo probe in Pr 1.85 Ce 0.15 CuO 4−y carried out by Zamborszky et al 18 and neutron scattering studies on Pr 0.88 LaCe 0.12 CuO 4−␦ by Dai et al 19 indicate that the electron-doped cuprates are, indeed, inhomogeneous though the origin of this inhomogeneous electronic configuration is undetermined at present. In a d x 2 −y 2-wave superconductor, the disorder can result in the localization of the quasiparticle excitations and may induce component of another symmetry pairing under some conditions.…”
Section: Introductionmentioning
confidence: 78%